051 Reducing particulate air pollution exposure in patients with coronary heart disease: improved cardiovascular health. (22nd September 2015) - Langrish, J P; Li, X; Wang, S; Lee, M M Y; Barnes, G D; Ge, G L; Miller, M R; Cassee, F R; Boon, N A; Donaldson, K; Li, J; Mills, N L; et al.
Abstract : Introduction: Particulate air pollution is a major public health concern and is associated with cardiovascular disease. In healthy volunteers, reducing particulate air pollution exposure attenuates exercise-induced increases in blood pressure and improves heart rate variability. In this study, we investigated the benefit of reducing exposure in patients with coronary heart disease. Methods: In an open-label randomised crossover trial, 98 patients with coronary heart disease walked on a predefined city centre route in Beijing in the presence and absence of a highly efficient facemask. Personal exposure to air pollution and exercise was assessed continuously using portable monitors and GPS tracking respectively. Blood pressure was measured using ambulatory blood pressure monitoring. Continuous 12-lead electrocardiography was carried out using a Holter monitor. Subjects' symptoms were assessed using a simple questionnaire. Results: The mask intervention was well tolerated and reduced general symptoms, perceived effort of work and perception of pollution (p<0.05 for all). Temperature (17.3±5.2 (mean±SD) vs 16.8±5.8°C) and relative humidity (30±14 vs 35±18 %) were similar in the presence and absence of the facemask respectively. Ambient particulate mass concentration (median 61 (IQR: 20 to 88) vs 89 (25 to 170) μg/m 3 ; PM2.5 ) and particle number (4.19±1.29 vs 4.39±1.45×10 4  particles/cm 3 ) were slightly lower during the mask visit, but based on efficacy studies, we predict the mask reduced the exposure further to 2 μg/m 3 and 1200 particles/cm 3 respectively. During the 2-h walk, exercise performed was identical on both visits. When subjects wore a facemask, mean arterial pressure was lower (93±10 vs 96±10 mm Hg; p=0.025) and heart rate was similar (p>0.05). During the 2-h walk, heart rate variability was increased (HF-power 54 (27 to 108) vs 40 (20 to 69) ms 2, p=0.005; HF/LF ratio 0.418 (0.258 to 0.712) vs 0.328 (0.207 to 0.573), p=0.004; RMSSD 16.7 (13.2 to 22.5) vs 14.8 (10.9 to 19.6) ms, p=0.007) when a facemask was worn. There were no differences in overall 24-h blood pressure, heart rate or heart rate variability. Maximal ST segment depression throughout the 24-h period was reduced when subjects wore a mask (−142 (−179 to −110) vs −156 (−202 to −123) μV; p=0.046) although there was no difference in the frequency of ST segment depression (>1 mm) episodes or symptoms of angina. Conclusions: In patients with coronary heart disease, wearing a facemask reduces symptoms and is associated with objective improvements in myocardial ischaemia, blood pressure and heart rate variability. This simple well-tolerated intervention has the potential to reduce the incidence of cardiovascular events in patients with coronary heart disease living in industrialised or urban environments.